KONSEP PENGEMBANGAN KONTRAKTOR SKALA KECIL - Surya Eka Priana (Ensiklopedia of Journal, 2019)
The development of small-scale contractor's capabilities is one of the efforts to empower weaker entrepreneurs. The impact of this development is expected to create jobs and increase community participation in rural and urban infrastructure development. Expected benefits with the development of small-scale contractor capabilities are to (1) Improve capacity and support the involvement of small-scale contractors in the implementation of construction services, (2) Improve the results of the implementation of small-scale contractors, (3) Infrastructure results from small-scale contractors can be used optimally , and (4) Small scale contractors are able to compete competitively and develop.